Association between Salivary Leptin Levels and Taste Perception in Children - Rodrigues, Lénia (2018)
The satiety inducing hormone leptin acts not only at central nervous system but also at peripheral level. Leptin receptors are found in several sense related organs, including the mouth. A role of leptin in sweet taste response has been suggested but, until now, studies have been based on in vitro experiments, or in assessing the levels of the hormone in circulation. The present study investigated whether the levels of leptin in saliva are related to taste perception in children and whether Body Mass Index (BMI) affects such relationship. Sweet and bitter taste sensitivity was assessed for 121 children aged 9-10 years and unstimulated whole saliva was collected for leptin quantification, using ELISA technique. Children females with lower sweet taste sensitivity presented higher salivary leptin levels, but this is only in the normal weight ones. For bitter taste, association between salivary leptin and caffeine threshold detection was observed only in preobese boys, with higher levels of salivary hormone in low sensitive individuals. This study is the first presenting evidences of a relationship between salivary leptin levels and taste perception, which is sex and BMI dependent. The mode of action of salivary leptin at taste receptor level should be elucidated in future studies.